(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Teacher motivation and effective training programs are essential for improving the quality of education and fostering professional growth among educators. This article explores the key components of teacher motivation, including intrinsic and extrinsic factors such as recognition, professional autonomy, supportive work environments, and opportunities for career advancement. It also outlines the critical features of successful teacher training programs, such as needs-based and personalized learning, technology integration, active and experiential learning, and ongoing professional development. The article highlights the interrelationship between motivation and training, emphasizing the need for continuous support and collaboration to ensure teachers remain engaged and effective in their roles. By addressing both motivation and training, educational institutions can create a dynamic environment where teachers are empowered to deliver high-quality education that meets the needs of diverse learners.